2020
DOI: 10.3390/nu12092525
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Interventions in the Management of Fibromyalgia Syndrome

Abstract: Fibromyalgia (FM) is a multifactorial syndrome of unknown etiology, characterized by widespread chronic pain and various somatic and psychological manifestations. The management of FM requires a multidisciplinary approach combining both pharmacological and nonpharmacological strategies. Among nonpharmacological strategies, growing evidence suggests a potential beneficial role for nutrition. This review summarizes the possible relationship between FM and nutrition, exploring the available evidence on the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 72 publications
(80 reference statements)
1
46
0
12
Order By: Relevance
“…There is an increasing evidence in the nutritional literature and authoritative reports about the concept of ultra-processed foods (UPF), recognized as an unhealthy diet. The evidence proves that high consumption of ultra-processed foods (UPFs) has a positive connection between UPFs consumption and the risk of multiple health effects, determined by an increase in non-communicable diseases, overweight and obesity [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing evidence in the nutritional literature and authoritative reports about the concept of ultra-processed foods (UPF), recognized as an unhealthy diet. The evidence proves that high consumption of ultra-processed foods (UPFs) has a positive connection between UPFs consumption and the risk of multiple health effects, determined by an increase in non-communicable diseases, overweight and obesity [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…Along the same lines, a systematic review concluded that pain and functional repercussion in FMS patients seem to improve with a hypocaloric diet, a raw vegetarian diet, or a low FODMAP diet, as much as quality of life, quality of sleep, anxiety, and depression and inflammatory biomarkers (Silva et al, 2019). Interestingly, another recent review indicated that, although the role of dietary supplements with vitamin D, magnesium, iron, and probiotic supplementation remains controversial, clinical trials show promising results (Pagliai et al, 2020). Furthermore, intervention based on the administration of olive oil, the replacement diet with ancient grains, low-calorie diets, the low FODMAP diet, the gluten-free, monosodium glutamate and aspartame-free, vegetarian, and Mediterranean diets all appear to be effective in reducing FMS symptoms (Pagliai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the management of FMS patients includes comprehensive assessment, goal setting, multimodal treatment including pharmacological and nonpharmacological therapies such as physical activity, behavioral therapy, sleep hygiene, dietary advice, and education regarding the disease and treatment approaches (Arnold et al, 2012;García-Ríos et al, 2019). It has been recently proposed that adherence to a healthy diet might be a promising strategy to improve FMS symptoms (Kaartinen et al, 2000;Lowry et al, 2020;Pagliai et al, 2020;Rossi et al, 2015;Ruiz-Cabello et al, 2017). Inflammation and oxidative stress are the main pathophysiological pathways of chronic pain and therefore a treatment program could include nutritional protocols to reduce the pro-inflammatory state and thereby alleviate pain (Dragan et al, 2020;Seaman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…En la sesión de la unidad de sueño se destacó la importancia del sueño reparador, la higiene y trastornos del mismo, las relaciones existentes entre sueño y percepción del dolor, entre calidad de sueño y alivio sintomático y, además, se informó sobre algunos tratamientos comunes (fitoterapia y melatonina) (20). Finalmente, la intervención nutricional subrayó el valor de la dieta equilibrada en la FM, el potencial antinflamatorio de la dieta mediterránea e incluyó recomendaciones específicas (intolerancias, sobrepeso, estreñimiento y reflujo gastroesofágico) (21).…”
Section: Materialses Y Metodounclassified